Potentiating Death and Governing Uncertain Futures: Guns, Assisted Dying and the Production of Sovereign Subjects - Dunseith, Bradley; Gandsman, Ari (Anthropologica, 2020)
<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Both gun rights advocates and right-to-die activists shape their moral selves through time in relation to a demand of personal autonomy. Practising autonomy – having a sense of control over one’s own life and death – becomes the principle of the good for both gun advocates and right-to-die activists. Though the ethical aims of both groups could not be more different, both movements produce a similar kind of subject. Whether through guns or end-of-life technologies, the person who has control over death has control over life, resulting in a subject actively working in and through time. However, while right-to-die activists take their own lives into their sovereign hands, gun owners engage with an ethics of time to prove their capacity in deciding who may live and who must die.